Interaction of cement particles with water or mechanism of hydration and hardening of cement - Vasiliy Agafonovich Lotov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2018)
The relevance of the research is caused by the necessity to deepen theoretical conceptions about the mechanism of cement water interaction for more efficient use of Portland cement. The aim of the study is to determine the behavior of the cement-water system during hydration and hardening with microcalorimetry new design. Object: Portland cement CEM 1 42,5 B (M500 D0). Methods: thermodynamic analysis of the cement-water system based on Gibbs equation, which is the combined expression of the first and the second laws of thermodynamics; calorimetric studies of the cement-water system with the original design of the differential microcalorimeter; magnetodynamic method of monitoring acoustic waves in the cement-water system. The results of the research. The paper demonstrates the possibility of using the basic law of thermodynamics in identifying the mechanism of cement hydration and hardening. It was found that the heat generated by cement hydration is consumed on dispersion of cement particles to nanoscale state. The surface and near-surface protonation of cement mineral particles play the main role in dispersing. Formation of cement stone structure begins with the unification of nanoscale particles in their recrystallization and transition to denser condition. This results in occurrence of free volume and free water in hardening system. Free water interacts with not hydrated surface of cement grains. This cement water interaction cycle is repeated throughout a long period of cement hardening and formation of cement stone structure. The dispersion of cement particles is accompanied by acoustic oscillations in the system frequency from 3-100 Hz to 20 kHz with intensity of low frequency oscillations of 3-10 decibels. Different periods of hydration are accompanied by vibrations of different intensity.